TEORI PSIKOLOGI POSITIF DALAM PETA ALIRAN-ALIRAN PSIKOLOGI PENDIDIKAN SERTA IMPLIKASINYA DALAM PENDIDIKAN ISLAM - Hadini Hadini (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
One of the streams that has managed to attract considerable attention to psychologists in the 21st century is the positive psychology school developed by Martin Seligmann. This theory has its own characteristics and has been empirically proven to be able to develop the potential of students. The great role of this theory in developing the potential of students is of course a modality that can be utilized in the world of Islamic Education today in order to assist its role in carrying out its duties to develop the potential of students. However, the problem that arises is that there is no clear map of the position of Positive Psychology theory among the existing schools of Educational Psychology theory which results in the blurring of the orientation of Education. Thus, of course, it is necessary to understand the position map of the theory among the various major schools of existing Educational Psychology theory, so that the implementation of education does not lose direction and footing. Based on the studies conducted in this paper, several important things were found, namely: first, Positive Psychology is a theory of optimizing human potential, it does not depart from mental disorders to normal, but it departs from normal conditions to mental health. Second, the theory of Positive Psychology is a bridge between Humanistic and Transpersonal schools. Positive Psychology Theory at a later stage has implications for the implementation of Islamic Education, where education is directed to theocentric and anthropocentric dimensions.